Research on the Prediction Model and Formation Law of Drying Cracks of Paddy Based on Multi-Physical Field Coupling - Hongchao Wang; Ziyu Wang; Gang Che; Lin Wan; Zhengfa Chen (Agriculture)
Cracking in paddy during processing and storage can significantly degrade its quality and economic value. This study elucidates the crack formation law in paddy across various drying stages through experiments and simulations that integrate multiple physical fields. A predictive model for crack occurrence, based on the relationship between the probability of cracking and drying time, is developed by introducing a critical moisture evaporation coefficient to delineate safe regio for cracking. The findings indicate a sharp increase in the percentage of drying cracks during the initial rapid drying phase, with continued escalation through the slower drying phase. The predictive model’s coefficient of determination exceeded 0.85, demonstrating its efficacy in forecasting crack progression. The primary driver for crack initiation and growth was identified as the cumulative effect of the moisture gradient, with the yield stress proving inadequate to counteract the stresses induced by this gradient, leading to cracking in paddy grains. These results furnish valuable insights for accurately predicting and managing crack development in paddy.